Overexpression of BubR1 Mitotic Checkpoint Protein Predicts Short Survival and Influences the Progression of Cholangiocarcinoma - Nongnapas Pokaew; Piya Prajumwongs; Kulthida Vaeteewoottacharn; Sopit Wongkham; Chawalit Pairojkul; Kanlayanee Sawanyawisuth (Biomedicines, 2024)
Budding Uninhibited by Benzimidazole-Related 1 (BubR1) or BUB1 Mitotic Checkpoint Serine/Threonine Kinase B (BUB1B) is an essential component of the spindle assembly checkpoint (SAC), which controls chromosome separation during mitosis. Overexpression of BubR1 has been associated with the progression of various cancers. This study demonstrated that high expression of BubR1 correlated with cholangiocarcinogenesis in a hamster cholangiocarcinoma (CCA) model and was associated with shorter survival in patients with CCA. Co-expression of BubR1 and MPS1, which is a SAC-related protein, indicated a shorter survival rate in patients with CCA. Knockdown of BubR1 expression by specific siRNA (siBubR1) significantly decreased cell proliferation and colony formation while inducing apoptosis in CCA cell lines. In addition, suppression of BubR1 inhibited migration and invasion abilities via epithelial–mesenchymal transition (EMT). A combination of siBubR1 and chemotherapeutic drugs showed synergistic effects in CCA cell lines. Taken together, this finding suggested that BubR1 had oncogenic functions, which influenced CCA progression. Suppression of BubR1 might be an alternative option for CCA treatment.